Social Death : Racialized Rightlessness and the Criminalization of the Unprotected - Cacho, Lisa Marie (Book collections on Project MUSE., 2012)
Social Death tackles one of the core paradoxes of social justice struggles and scholarship-that the battle to end oppression shares the moral grammar that structures exploitation and sanctions state violence. Lisa Marie Cacho forcefully argues that the demands for personhood for those who, in the eyes of society, have little value, depend on capitalist and heteropatriarchal measures of worth. With poignant case studies, Cacho illustrates that our very understanding of personhood is premised upon the unchallenged devaluation of criminalized populations of color. Hence, the reliance of rights-b.